Internally hollow Cu2O nanoframes with the abundance of {110} facets enhance direct propylene epoxidation - Yueming Qiu; Yichen Zhang; Ronghui Zhang; Meng Huang; Kok Bing Tan; Guowu Zhan; Gang Fu; Qingbiao Li; Jiale Huang (Nature Communications)
Abstract The gas-phase direct epoxidation of propylene (DEP) using molecular oxygen, which has been deemed the ‘dream reaction’ for propylene oxide (PO) production due to its efficiency and environmental benefits, remains highly regarded by researchers. In this contribution, we engineer a series of Cu2O nanocatalysts by employing the ligand-protection/selective facet-etching technique. Among these, the internally hollow Cu2O nanoframes, featuring increased specific surface area and a prevalence of {110} sites, achieve a triple-win in activity, selectivity, and stability, with an optimal PO formation rate of 0.18 mmol gcat -1 h-1 and a selectivity of 83.8% at 175 °C. In addition, long-term tests confirm that these internally hollow nanoframes maintain high activity and selectivity for over 300 minutes. Further characterizations, combined with density functional theory calculations, confirm that the unique atomic arrangement of copper and oxygen on the Cu2O {110} facet facilitate the formation of chemically adsorbed oxygen species and propylene oxide as well. We anticipate that the ligand-protection/selective facet-etching approach may serve as a versatile method for fabricating well-defined catalyst architectures.